(untitled) - Baumol, William J. (Australia, 2005)
Baumol (economics, New York U. and Princeton U.) and Blinder (economics, Princeton U.) present this economics textbook, which begins with an introduction to the topic and ends with a discussion of the US in the world economy. In this edition, they simplify the chapters on stock and bond markets, regulation and antitrust, environmental economics, and poverty and inequality. They have also brought back the myth and reality chapter that was omitted from the ninth edition. Other new material has been added, some chapters have been reorganized, and updates to the section on microeconomics and the virtues and limitations of markets have been made.
Keywords: Economics